Dampak Ekonomi Pembangunan Ekowisata Habitat Bekantan bagi Masyarakat (Studi Kasus di Desa Panjaratan Kecamatan Pelaihari Kabupaten Tanah Laut) - Lestari, Agustina; Rizali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research was conducted to determine how much the people of Panjaratan Village felt the impact of the development of the Bekantan Habitat Ecotourism in terms of income and job opportunities. This study uses a qualitative descriptive technique in collecting data, namely by observation, interviews, and documentation. Interviews were conducted with influential parties in the village who felt directly the impact they received from the tourism development. The results showed that the respondents agreed that tourism development impacted income and job opportunities for the community. However, the existence of tourism has not been able to increase the community's standard of living because tourism is still under development.